Philosophy of Theoretical Mysticism - Muhammad Fanai Ishkawari (حکمت اسرا)
Mysticism (or gnosis, ÝirfÁn) is multi-dimensional. Its primary and most important dimensions are cognitive (vis-à-vis theoria) and conative (vis-à-vis praxis). A study of the various dimensions of mysticism has led to the formation of a number of branches of science, which can be called “mystical sciences.” The most important branches of science of mysticism in the Islamic tradition are: theoretical mysticism and practical mysticism. With the advent and currency of second-order philosophies[1] in the West—those supra-speculative philosophies that survey matters from the outside—the phenomena of mysticism was also considered and intellectually examined from the outside, leading to the appearance of a branch of knowledge called the ‘philosophy of mysticism.’ This new science applies itself to the nature and methodology of mystical experience and its principles. Alongside this branch, another independent branch of science can be envisioned that studies the quiddity and manner of theoretical mysticism, asking the relevant questions as regards it subject matter, bases, issues, methodology and structure. We call this branch of knowledge the ‘philosophy of theoretical mysticism.’ While this type of discussion has traditionally and generally been treated of in the introductions of some relevant books in the field, the expansion of this branch of knowledge and the tabling of fundamental questions and doubts with regards to its nature, bases, and premises calls for independent treatment. The article at hand is a general survey of some of the most important lines of inquiry in the philosophy of theoretical mysticism.